Psychological Health and Optimism amongst Unemployed Graduates in Zimbabwe - Julia Mutambara; Tinashe R. Makanyanga; Pilot Mudhovozi (Journal of Student Affairs in Africa, 2019)
The study sought to examine the relationship between optimism and general health amongst unemployed graduates in Zimbabwe. Most of the studies on unemployment have focused on job loss but this study is based on failure to get employment after graduating with a university degree in a resource-constrained environment. One hundred and twelve (112) graduates were selected using non-probability sampling methods. A self-administered questionnaire was used to collect data and the Statistical Package for Social Sciences (SPSS) was utilised to analyse data. Age and period after graduation were found to be negatively related to both general health and optimism amongst the unemployed graduates. Overall optimism and general health were found to be inversely related. The study calls for the need for psychological interventions for unemployed graduates in Zimbabwe.